Model struktur pengaruh kecerdasan emosi dan kecerdasan spiritual terhadap kepimpinan transformasi Ketua Jabatan Akademik - Mohd. Said, Siti Zunariah (2013)
This research examines the influence of emotional intelligence and spiritual intelligence on transformational leadership among the heads of departments in polytechnics from the southern zone of Peninsular Malaysia. This study also examines the relationship between each aspect of emotional intelligence and spiritual intelligence, the relationship between emotional intelligence and spiritual intelligence, and identifies the subscales of emotional intelligence and spiritual intelligence that can predict transformational leadership behaviors. Data collection for this study is carried out through survey method. The quantitative data was analyzed by using Pearson Correlation, Multiple Regressions Analysis, Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). A total of 319 lecturers from polytechnics in southern zone of Peninsular Malaysia were selected as respondents using stratified sampling method. The instruments utilized were Emotional Quotient Index (EQI), Integrated Spiritual Intelligence Scale (ISIS) 360° and Multifactor Leadership Questionnaire (MLQ). The findings reveal that there is a significant relationship between each construct of emotional intelligence and each construct of spiritual intelligence. The research also indicates that there is a significant high relationship between emotional intelligence and spiritual intelligence. The multiple regression analysis in this research shows that constructs of emotional intelligence specifically self-awareness, self-regulation and self-motivation play significant roles in influencing transformational leadership. As for the constructs of spiritual intelligence, integrity/holism and consciousness influence transformational leadership. However, the structural equation modeling (SEM) depicts only the emotional intelligence can predict transformational leadership but the spiritual intelligence is not a significant predictor to transformational leadership. The implications of this research show that the need for evaluation of the training and career development program as well as the criteria for the head department selection based on emotional and spiritual intelligence aspects.